Age, Geochemistry and Origin of the Ardara Appinite Plutons, Northwest Donegal, Ireland - Murphy, J.Brendan; Nance, R.Damian; Gabler, Logan B.; Martell, Alexandra; Archibald, Douglas A. (Geoscience Canada)

(untitled) (The Geological Association of Canada, 2019)
In northwest Donegal, Ireland, a large number of coeval appinitic (hornblende-plagioclase-rich) plutons and lamprophyre dykes occur around the Ardara pluton, a granitic satellite body and one of the oldest phases of the ca. 428–400 Ma composite Donegal Batholith. The appinite units form a bimodal (mafic–felsic) suite in which hornblende is the dominant mafic mineral and typically occurs as large prismatic phenocrysts within a finer grained matrix. Lamprophyre dykes are mafic in composition with a geochemistry that is very similar to that of the mafic appinite bodies. Both mafic rocks are subalkalic, with calc-alkalic and tholeiitic tendencies, and show trace element abundances indicating that the mantle source was contaminated by subduction zone fluids. 40Ar/39Ar analysis of hornblende separated from two samples of appinite yield mid-Silurian (434.2 ± 2.1 Ma and 433.7 ± 5.5 Ma) cooling ages that are interpreted to closely date the time of intrusion. Hence, according to the available age data, the appinite bodies slightly predate, or were coeval with, the earliest phases of the Donegal Batholith. Sm–Nd isotopic analyses yield a range of initial εNd values (+3.1 to –4.8 at t = 435 Ma) that, together with trace element data, indicate that the appinitic magmas were likely derived from melting of metasomatized sub-continental lithospheric mantle and/or underplated mafic crust, with only limited crustal contamination during magma ascent. The appinitic intrusions are interpreted to have been emplaced along deep-seated crustal fractures that allowed for mafic and felsic magma to mingle. The magmas are thought to be the products of collisional asthenospheric upwelling associated with the closure of Iapetus and the ensuing Caledonian orogeny, either as a result of an orogen-wide delamination event or as a consequence of more localized slab break-off.